Women in Otolaryngology: Experiences of Being Female in the Specialty. (23rd July 2020) - Lawlor, Claire; Kawai, Kosuke; Tracy, Lauren; Sobin, Lindsay; Kenna, Margaret
Abstract : Objectives: A broad survey of women otolaryngologists on the current state of the field, including opportunities for advancement, support of family leave, and prevalence of harassment, has not been performed since 1998. An update on the experiences of female otolaryngologists is vital to continue to advance the specialty. Study Design: Anonymous web‐based survey. Methods: Survey of members of the Women in Otolaryngology (WIO) section of the American Academy of Otolaryngology–Head and Neck Surgery (all members of the AAO‐HNS that identify as female are automatically members of this section). Distributed via AAO‐HNS. Results: Five hundred thirty‐five responses out of 2303 total WIO members (response rate of 23.2%). Respondents ranged in age from 25 to >65 years. Respondents reported that in the residency programs they attended, 29% of residents, 13% of faculty, and 7% of department leaders were women. Forty‐four percent disagreed that their department leaders and 39% disagreed that their male co‐residents were supportive of women starting families in training. Younger respondents were more likely to feel that their department leaders were supportive of female residents, maternity leave, etc. Harassment in the current work environment did not differ by age; 53% reported harassment‐free, 31% subtle undertones, 8% noticeable tones, 2% significant harassment. Harassment in the workplace varied by region; the greatest level of harassment was in the Midwest. Conclusions: Women otolaryngologists continue to experience harassment in the workplace. It is encouraging that younger otolaryngologists feel more supported by their departments in both their careers and their personal lives. This survey highlights critical areas for continued growth within our specialty. Level of Evidence: IV Laryngoscope, 131:E380–E387, 2021